2004
DOI: 10.1111/j.1708-8208.2004.tb00217.x
|View full text |Cite
|
Sign up to set email alerts
|

Bone Reformation with Sinus Membrane Elevation: A New Surgical Technique for Maxillary Sinus Floor Augmentation

Abstract: The study showed that there is great potential for healing and bone formation in the maxillary sinus without the use of additional bone grafts or bone substitutes. The secluded compartment created by the elevated sinus membrane, implants, and replaceable bone window allowed bone formation according to the principle of guided tissue regeneration. The precise mechanisms are not known, and further histologic studies are needed. Sinus membrane elevation without the use of additional graft material was found to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
263
3
9

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 235 publications
(292 citation statements)
references
References 9 publications
16
263
3
9
Order By: Relevance
“…13,14 Considering the results of this study, all sinus floor elevation procedures showed substantial new bone formation in both study groups. In this controlled and randomized clinical study evaluating bone formation, the new bone formed with the lateral sinus floor elevation seen on CT scan imaging presented a high density.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…13,14 Considering the results of this study, all sinus floor elevation procedures showed substantial new bone formation in both study groups. In this controlled and randomized clinical study evaluating bone formation, the new bone formed with the lateral sinus floor elevation seen on CT scan imaging presented a high density.…”
Section: Discussionmentioning
confidence: 91%
“…12 In a recent study, 19 implants were inserted in 12 sinuses without any grafting material. 13 The authors did not report any implant loss and advocated that no grafting material was needed for sinus floor elevation. Using a bone graft substitute instead of autogenous bone eliminates the need to harvest the patient's own bone, thus potentially reducing the risk and pain associated with the harvest procedure.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In 2004, they described a new surgical technique for maxillary sinus augmentation with only sinus membrane elevation and replacement of the bony window 5 . The replacement of the bony window could have been another factor in bone formation by preventing soft-tissue growth into the sinus, which would disturb the maintenance of the secluded space 4,5 . Surgical trauma to the maxillary sinus could also have contributed, as explained in the study on the situation after the Caldwell-Luc operation 9 .…”
Section: Discussionmentioning
confidence: 99%
“…Achieving bone formation in defects via the innate ability of local tissues such as periosteum and the schneiderian membrane without introduction of a graft has been documented since early 2000. Lundgren and colleagues 19 described the formation of new bone in the sinus simply by doing a sinus lift. No graft material or exogenous bone growth-promoting factors were placed in the wound.…”
Section: Surgical Techniques Suggested Bone-grafting Protocolmentioning
confidence: 98%